IMPLEMENTASI ALGORITMA PAILLIER CRYPTOSYSTEM PENGAMANAN CITRA DIGITAL PADA APLIKASI CHAT - Juni Ade Nawer Purba; Taronisokhi Zebua; Rivalri K Hondro (STMIK Budi Darma, 2019)
Chat application allows easily users to exchange information in the form of text, images, video and audio. Information that is distributed can be either confidential or not confidential. However, at this time there is often attack on to information that is communicated through communication media such as chat, so that it is possible for other people to misuse the information. The use of algorithms from cryptographic techniques in securing distributed information. This research discusses how to use the cryptosystem pailler algorithm to secure digital images that are distributed through chat applications. This algorithm is very resistant to solving because n-residue class calculations are believed to be very difficult to compute, so as to maintain the security of images distributed through chat applications.Keywords: Cryptography, Paillier Cryptosystem, Chatting, Digital Image, Communication